Gender Comparisons of Asymmetric Lateralization in Neurodegenerative Disorder Patients via E-Pen Based Cognitive Assessment System - Haemi JEE; Jaehyun PARK (Tehran University of Medical Sciences, 2019)
Background: The clinical gender-dependent characteristics of visuospatial neglect between men and women have not been elucidated in Korean patients with cognitive impairment. The goal of this study was to observe the asymmetric lateralization in patients using a novel e-pen based cognitive assessment system. Methods: A total of 31 patients, 16 men and 15 women, with early stage hemispheric cerebral dysfunction were recruited for the assessment of unilateral neglect suing a novice paper-and-pencil based electronic evaluation system from a rehabilitation center of Inha University hospital in 2016. Results were assessed for degrees of deviations, and numbers of neglected lines. Degree of deviation was assessed using the positions and distances from the horizontal line centers. Effect sizes were calculated to assess proximities between the assessed results. Results: Comparatively greater left and rightward biasness for the right-sided and left-sided horizontal lines were observed for the male patients, respectively. Moreover, greater degree of left to rightward biasness was observed as the horizontal lines shortened in both groups. However, the magnitude of biasness in female patients showed comparatively less directional bias, indicating greater prevalence for the center of mass effect in male patients. Conclusion: Gender difference in visuospatial neglect seems to exist with less accuracy in recognition for the bisecting center for the female and asymmetrical lateralization and magnitude of deviation for the male patients.